Viewpoint of probabilistic risk assessment in artificial enabled social engineering attacks - Nik Zulkarnaen Khidzir (Tanjong Malim, 2019)
Viewpoint of probabilistic risk assessment in artificial enabled social engineering attacks by Nik Zulkarnaen Khidzir